Levantamento e caracterização da população ex-situ da raposa-do-campo (Lycalpex vetulus) no Brasil - Morais, Luan Henrique (2023)
Carnivores suffer several forms of pressure contributing to the decline of these populations. The hoary fox (Lycalopex vetulus) is the smallest of the Brazilian canids. Have crepuscular-nocturnal habits, are omnivorous and monogamous, and their reproductive period occurs once a year, borning three to five offspring. Human actions accelerate the extinction process, where 25% of fauna and flora species are vulnerable. The hoary fox is classified as vulnerable mainly due to habitat loss and fragmentation. It is endemic to the Cerrado, a biome that has been losing significantly its area to pastures and agricultural activities. Integrated strategies between institutions may be the only alternative for the survival of endangered species. Knowing the biology of the species, real threats, correctly identifying of the specimens and having an overview of the captive individuals, in addition to generating knowledge, is of paramount importance in the creation of strategies aimed at the conservation of Lycalopex vetulus. Through and with the participation of the Association of Zoos and Aquariums of Brazil (AZAB) and the São Paulo Association of Zoos and Aquariums (APAZA), a consultation was carried out with the associated institutions that keep the species under guard, and that showed interest in participating in the study. A questionnaire was prepared with population data and questions related to ex situ management, including information on nutrition, facilities, behavior, education, physical restraint, veterinary care, management and reproduction. Photos were also requested to identify individuals. The answers were qualitatively evaluated in order to know the management that the institutions offer to the animals. For the classification of individuals, the requested photos were evaluated in order to prove, from the phenotypic characteristics, whether the animals in question were L. vetulus or were mistakenly classified. In relation to the 24 animals participating in the project, only five had phenotypic characteristics consistent with the species under study, two are more similar to L. gymnocercus and the rest of them have characteristics of the two species, which may be hybrids between these species. It is concluded that it is of paramount importance to train professionals who work with fauna to correctly identify the species, as well as carrying out a molecular evaluation of individuals kept under human care, in order to have precision of the species for the beginning of an effective integrated conservation project that aims to preserve it.